2023
DOI: 10.1007/s00167-023-07501-0
|View full text |Cite
|
Sign up to set email alerts
|

High degree of consensus on diagnosis and management of rotator cuff tears: a Delphi approach

Abstract: Purpose To develop a consensus on diagnosis and treatment of rotator cuff tears. The study focused on selected areas: imaging, prognostic factors, treatment options, surgical techniques. Methods Panel was composed of all members of the shoulder committee of the Italian Society of Arthroscopy, Knee, Upper arm, Sport, Cartilage and Orthopedic techniques (SIAGASCOT). Four rounds were performed. The first round consisted of gathering questions which were then divided into seven blocks referring to: imaging, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Therefore, a reliable method to predict the possibility of irreparability and healing failure after ARCR would help surgeons plan surgical procedures and counselling patients [31,45]. Notably, many studies have identified that retraction of the rotator cuff tendon, determined by preoperative magnetic resonance imaging (MRI), is crucial in predicting reparability and tendon healing after ARCR [1,6,11,19,21,34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a reliable method to predict the possibility of irreparability and healing failure after ARCR would help surgeons plan surgical procedures and counselling patients [31,45]. Notably, many studies have identified that retraction of the rotator cuff tendon, determined by preoperative magnetic resonance imaging (MRI), is crucial in predicting reparability and tendon healing after ARCR [1,6,11,19,21,34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The other method is a layered suture under arthroscopy, which adheres to the original anatomical structure of the rotator cuff by separately fixing the synovial sac of the rotator cuff and the lateral aspect of the joint. No significant difference was observed between separate and en bloc repairs [11, 12], it is unclear if tendon delamination affects rotator cuff repair healing and clinical outcomes. Delamination is a risk factor for poor clinical and anatomical outcomes after rotator cuff repair [2, 13, 14].…”
Section: Introductionmentioning
confidence: 99%